Riesgos psicosociales e integración profesional de médicos extranjeros: un estudio sobre el manejo del conflicto en la zona central de Chile - Lazzaro-Salazar, Mariana (2017)
The way in which communicative conflicts are confronted, as part of the acculturation process, can constitute a psychosocial risk factor that may affect the effectiveness of health care delivery. Aim: To describe the levels of dominance, adaptability and evasion as indicators of the way in which conflict situations are faced in the workplace by foreign physicians in the management of communicative conflicts. Materials and methods: A self-report questionnaire was answered by 51 foreign physicians (63% women, 76% Venezuelans, 64% aged between 31 and 40 years old) who work in public healthcare institutions in a southern region of Chile. Results: The highest scores were recorded for the adaptable style of conflict management (69%), while the lowest scores were recorded for the evasive style (6%). Higher levels of dominance were identified for women than for men. There was a positive association between dominance and time progression, where the level of dominance increased as participants gained greater professional experience and workplace seniority. Conclusions: The foreign physicians who participated in this study have a clear constructive attitude towards the negotiation of conflicts. However, this effort to adapt can also become a psychosocial risk factor that affects professional integration in intercultural workplace contexts.